The combination of sodium perborate and water as intracoronal teeth bleaching agent - Ananta Tantri Budi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: The color change on post-endodontic treated teeth can be overcome by intracoronal tooth bleaching using walking bleach. Some agents used in walking bleach are combination of sodium peroxide and hydrogen peroxide, and combination of sodium perborate and water. Purpose: The objective of this review is to provide information and consideration of using safe and effective bleaching agents in the field of dentistry. Reviews: On one side, the use of sodium perborate and water combination does not cause the reduction of dentin hardness, enamel decay, and root resorbtion. On the other side, the use of sodium perborate and 30% hydrogen peroxide combination indicates that it takes longer time in yielding the proper color of teeth. Conclusion: The use of sodium perborate and water combination as bleaching agents is effective and safe.